Linguopoetic analysis of John Steinbeck’s novels (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Linguopoetics deals with the poetic meaning of words and phrases in the literary works. It focuses on stylistic devices and expressive means utilized by the writer. The author analyzed the linguopoetical features of John Steinbeck’s novels and identified the typical features of the writer. The examples extracted from the novel played an important role in proving the theoretical findings of the author.